2015
DOI: 10.1155/2015/905897
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Body Positions on Bioelectrical Activity of the Pelvic Floor Muscles in Nulliparous Continent Women

Abstract: We examined pelvic floor muscles (PFM) activity (%MVC) in twenty nulliparous women by body position during exercise as well as the activation of abdominal muscles and the gluteus maximus during voluntary contractions of the PFMs. Pelvic floor muscle activity was recorded using a vaginal probe during five experimental trials. Activation of transversus abdominis, rectus abdominis, and gluteus maximus during voluntary PFM contractions was also assessed. Significant differences in mean normalized amplitudes of bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 27 publications
(58 reference statements)
3
42
1
1
Order By: Relevance
“…From a total of 20 included studies, four (8,9,32,39) recorded the activity of all AbMs (TrA, RA, OI, and OE) during PFM contraction, and 19 studies provided instructions to contract the PFMs and recorded the AbM coactivity (8,9,22-35,37-39). Fifteen studies (8,9,22-24,26,28,31-37,39) reported the MVC of the PFMs. Three studies (23,27,34) considered the standing position for the assessment of the coactivity, and another eleven studies considered the supine position (8,9,22,25,29-31,35-38).…”
Section: Resultsmentioning
confidence: 99%
“…From a total of 20 included studies, four (8,9,32,39) recorded the activity of all AbMs (TrA, RA, OI, and OE) during PFM contraction, and 19 studies provided instructions to contract the PFMs and recorded the AbM coactivity (8,9,22-35,37-39). Fifteen studies (8,9,22-24,26,28,31-37,39) reported the MVC of the PFMs. Three studies (23,27,34) considered the standing position for the assessment of the coactivity, and another eleven studies considered the supine position (8,9,22,25,29-31,35-38).…”
Section: Resultsmentioning
confidence: 99%
“…The Levator ani muscles are constantly active, even at rest [15,31,40], which keeps the urogenital hiatus closed [3]. Women without PFM dysfunction counteract their IAP during common activities with an unconscious automatic increase in PFM activity [33,40].…”
Section: Discussionmentioning
confidence: 99%
“…Surface electromyography is among the modalities to investigate the function of the pelvic floor muscles in real time [ 25 ]. sEMG was used to evaluate pelvic floor muscles’ activity in nulliparous, asymptomatic women by body position during voluntary contractions of the PFMs [ 26 ]. The reliability of repeated surface electromyography of the pelvic floor muscles was confirmed in young continent women based on the analysis of the resting, mean and peak amplitudes, time before peak and area [ 27 ].…”
Section: Discussionmentioning
confidence: 99%